Rhetoric or reality?: victims' enforcement mechanisms in England and Wales and the United States - Manikis, M (2014)
Recent policies in England and Wales and the United States have recognised for the first time enforcement mechanisms for victims of crime under the Crime Victims’ Rights Act (CVRA) in the United States as well the Code of Practice for Victims of Crime in England and Wales (the Code). Although very different from one another, these policies ostensibly aimed to provide a stronger commitment to victims’ rights, by recognising an accessible, timely and impartial process that recognises accountability and provides individual remedies in cases of breaches. This thesis engages in a careful in-depth analysis of these mechanisms and their implementation based on elite qualitative interviews, case law analysis and a multidisciplinary examination of the relevant literature. It argues that on the whole, these mechanisms have presented a number of limitations, and thus in many respects cannot and have not delivered accessible, and timely means to respond to victims’ rights breaches. Most importantly, it demonstrates that for certain types of breaches and in certain contextual settings, these mechanisms have recognised only limited or no redress at all for breaches. This research takes the available victims’ literature further by arguing that many of these promises have been closer to rhetoric than reality and providing a more nuanced portrait of the substantial difficulties and limitations that relate to these enforcement mechanisms. In effect, these limitations can be understood in light of the nature and structural components of these selected mechanisms, as well as the ways they have been implemented by the main actors involved in these processes and the different contexts under which the different types of breaches take place. Finally, despite their limitations, when compared to one another, each mechanism can be considered a better option for access, timeliness and redress – depending on context and the type of breach. Following from this analysis, a complementary approach is developed which can facilitate and increase opportunity for redress for a wider range of situations. It is important to bear in mind however the limits of the complementary approach; namely, that it only includes elements inspired from the two mechanisms examined in this thesis and that there are several limitations that relate to transplants and policy transfers.